Analisis Penerimaan Sistem Informasi Laboratorium di Perguruan Tinggi Vokasi - Agung Raharjo, Muhammad; Octavianie, Adhitya; Fadhilah Nugrah, Andi (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2021)
Makassar Aviation Polytechnic has a number of laboratory facilities with a high level of utility, where the availability of facilities and infrastructure aspects is very important in the laboratory. The use of information systems is needed to be able to manage facilities better, therefore before this system is fully implemented, it is necessary to analyze the behavior of information system users, so that it can be accepted by users of information systems at the Makassar Aviation Polytechnic. The approach used in this study with the Technology Acceptance Model (TAM) consists of perceived usefulness and perceived ease of use, using the Guttman scale measurement. The results of this study showed that the perceived usefulness factor of most educators and cadets gave a positive perception of using laboratory information systems, while the perceived easy of use factor gave a negative perception of the laboratory information system because it was not fully able to use the laboratory information system. used by educators and cadets due to the absence of accessible features to facilitate the use of the laboratory.